Lethal and sublethal effects of chemical and bio-insecticides on Spodoptera frugiperda adults: new perspectives for “attract-and-kill” control strategies - El-Said, Nourhan A.; Alfuhaid, Nawal AbdulAziz; Chellappan, Biju Vadakkemukadiyil; El-Beltagi, Hossam S.; El-Mogy, Mohamed M.; Moustafa, Moataz A. M. (Frontiers in Plant Science, 2025)
Spodoptera frugiperda (Lepidoptera: Noctuidae), commonly known as the fall armyworm, is a highly destructive migratory insect that poses a serious risk to global agricultural production, particularly maize crop. Targeting adult stages through ingestion-based control strategies offers a promising alternative to conventional broad-spectrum insecticide applications. In the current research, the lethal and sublethal impacts of five insecticides were evaluated against adult S. frugiperda, with a particular focus on chlorantraniliprole. Of the tested compounds, chlorantraniliprole revealed the highest toxicity (LC50 = 1.29 mg/L). Sublethal exposure to chlorantraniliprole significantly reduced larval and pupal development durations, decreased pupal weights, and shortened adult longevity in the offspring, without significantly affecting larval mortality, pupation rate, or emergence rate. Enzymatic assays showed a minimal induction of detoxification enzymes, suggesting a lower likelihood of rapid resistance emergence. This underscores the promise of chlorantraniliprole as an effective, environmentally favorable agent for integration into attract-and-kill strategies aimed at the sustainable control of S. frugiperda infestations.